Clinical Manifestation of a Calyceal Diverticular Abscess in a Pregnant Woman. (30th November 2014) - Sekiguchi, Masaki; Hasegawa, Yuichi; Kinomoto, Satoko; Sago, Haruhiko
Abstract : Calyceal diverticula are congenital, nonsecretory abnormalities in which the transitional cell-lined cavity communicates with the renal collecting system. Here we present the case of a calyceal diverticular abscess during pregnancy. A 40-year-old primiparous woman developed the abscess at 23 weeks of gestation, with right flank pain and a 37.8°C fever. A transabdominal ultrasound revealed a12 × 10 cm cystic mass in the right kidney. She was initially diagnosed with a simple renal cyst infection, and intravenous antibiotics were initiated. Percutaneous drainage was started at 26 weeks of gestation. When urine excretion from the cyst was confirmed by dye test using indigotindisulfonate sodium, the patient was diagnosed with a calyceal diverticular abscess. She gave birth to a 2, 870 g healthy male at 38 weeks of gestation. Percutaneous drainage with low-dose antimicrobial therapy could thus allow for the continued pregnancy of women with a calyceal diverticular abscess until full term.